Lipid abnormality in diabetic kidney disease and potential treatment advancements - Tu, Qian Ming; Jin, Hui Min; Yang, Xiu Hong (Frontiers in Endocrinology, 2025)
Numerous studies have shown that dyslipidemia increases the risk of atherosclerotic cardiovascular disease (ASCVD) and significantly impacts the occurrence and progression of diabetic kidney disease (DKD). Early interventions for lipid metabolism disorders in DKD may improve renal function. This article reviews the clinical characteristics of dyslipidemia, mechanisms of lipid-induced renal injury, and advances in lipid-lowering therapy in DKD. We searched PubMed, Web of Science, and EMBASE to identify relevant articles, using keywords such as “diabetic kidney disease”, “diabetic nephropathy”, “diabetes”, “dyslipidemia”, “kidney”, “cardiovascular disease”, and “lipid therapy”. High triglyceride (TG) and low high-density lipoprotein (HDL) are associated with increased risks of albuminuria and estimated glomerular filtration rate (eGFR) decline. Abnormal lipid metabolism may damage glomerular podocytes and renal tubular epithelial cells via ectopic lipid deposition, eventually impairing glomerular filtration function and increasing urinary albumin excretion. Lipid-lowering therapies can ameliorate lipid accumulation, downregulate inflammatory mediator expressions, and alleviate renal fibrosis. Fibrate and statin applications exhibit beneficial effects, reducing albuminuria and slowing eGFR decline in early DKD. However, the long-term effects of statins and fibrates on renal outcomes remain controversial. Pro-protein convertase subtilisin/kexin 9 (PCSK9)-targeted interventions have minimal side effects on the kidneys and seem effective in reducing inflammation and improving renal impairment compared with statins and fibrates. In addition, LDL apheresis (LDL-A) and double filtration plasmapheresis (DFPP) are promising clinical applications in diabetic patients with severe hypercholesterolemia or lipid-lowering drug intolerance.